Analisis Perencanaan Strategis Sistem Informasi dengan Metodologi Tozer pada Sabisu Interior - Sri Anardani; Latjuba Sofyana STT; Yessi Yunitasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Sabisu Interior is an interior design service company located in Ngawi Regency. The operational management of ordering Sabisu Interior services has not yet used an information system. Problems arise because of the increasing number of customers and demand for the number of orders. Order, production and financial data management is still carried out by recording it in Microsoft Office applications. his raises the problem of discrepancies between order data, production data and financial data. In this research, a strategic planning of information systems and information technology will be carried out using the Tozer method. Several analysis tools are used such as Value Chain, PEST, CSF and Mc. Farlan Strategic Grid to provide an overview of IS/IT implementation. The research objective is to produce a portfolio of IS/IT strategic planning models that support Sabisu Interior's business strategy and vision and mission. The formulation of IS/IT strategic planning using the tozer method in this study produced an IS/IT strategic planning portfolio document. The results of this research in the form of a portfolio document contain 9 proposals for implementing IS/IT which will be used as recommendations for Sabisu Interior to make decisions regarding the development of IS/IT for the company in the future.